1994
DOI: 10.1111/j.1558-5646.1994.tb05312.x
|View full text |Cite
|
Sign up to set email alerts
|

THE GENETICS OF VIABILITY IN DROSOPHILA MELANOGASTER : EFFECTS OF INBREEDING AND ARTIFICIAL SELECTION

Abstract: Inbreeding and artificial selection experiments were conducted to investigate the genetic properties of egg-to-pupa viability in a population of Drosophila melanogaster. The effect of different levels of inbreeding (F = 0, 0.25, 0.50, and 0.73) was studied. Up to F = 0.50, a linear depression of the mean viability was observed, accompanied by a significant increase of both within-line additive variance and between-line variance. At F = 0.73, no further changes were detected. This can be attributed to natural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
64
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 23 publications
(18 reference statements)
10
64
0
Order By: Relevance
“…In Drosophila melanogaster, inbreeding and artificial selection experiments have also been carried out to investigate the genetic properties of fecundity and (1) viability (Rose, 1984;López-Fanjul & Villaverde, 1989;Garcia et al, 1994). For both traits, the results are compatible with the genetic variance in popula- (2) tions being generated by segregation at a few loci C The Genetical Society of Great Britain, Heredity, 75, 376-381.…”
Section: Discussionsupporting
confidence: 60%
“…In Drosophila melanogaster, inbreeding and artificial selection experiments have also been carried out to investigate the genetic properties of fecundity and (1) viability (Rose, 1984;López-Fanjul & Villaverde, 1989;Garcia et al, 1994). For both traits, the results are compatible with the genetic variance in popula- (2) tions being generated by segregation at a few loci C The Genetical Society of Great Britain, Heredity, 75, 376-381.…”
Section: Discussionsupporting
confidence: 60%
“…These findings have been supported to some extent by empirical studies on model organisms (e.g., García et al 1994;Fernandez et al 1995;Whitlock and Fowler 1999). Hallander and Waldmann (2007) investigated the importance of nonadditive genetic interactions when truncation selection was applied to a breeding population.…”
supporting
confidence: 56%
“…Life history traits closely associated with fitness are, on average, more likely to show an increase in V A after a bottleneck than morphological traits Willi et al 2006), probably because life history traits are more likely to have a nonadditive genetic architecture than morphological traits (Roff and Emerson 2006). While V A was higher in the bottleneck lines than in control lines, these empirical studies were unable to show whether adaptability had increased; where an increase in V A for a fitness trait was found (Lopez-Fanjul and Villaverde 1989;Garcia et al 1994;Fernandez et al 1995;Wade et al 1996;Briggs and Goldman 2006), this increase was accompanied by inbreeding depression, as predicted by an increased expression of recessive deleterious alleles (Wang et al 1998). However, more empirical data on the role of dominance and epistasis for adaptive evolution in small populations and on traits of ecological relevance are needed.…”
mentioning
confidence: 62%
“…Empirical studies on laboratory populations have reported an increase in V A following a population bottleneck in several species, for morphological traits (Bryant et al 1986;Whitlock and Fowler 1999) as well as life history traits (Lopez-Fanjul and Villaverde 1989;Garcia et al 1994;Fernandez et al 1995;Briggs and Goldman 2006). Life history traits closely associated with fitness are, on average, more likely to show an increase in V A after a bottleneck than morphological traits Willi et al 2006), probably because life history traits are more likely to have a nonadditive genetic architecture than morphological traits (Roff and Emerson 2006).…”
mentioning
confidence: 99%